Enabling modernisation, marginalising alternatives? Kenya's agricultural policy and smallholders. (6th June 2022) - Ajwang, Fredrick; Arora, Saurabh; Atela, Joanes; Onyango, Joel; Kyari, Mohammad
Abstract: To address intensifying social and environmental challenges, development policy must learn from inclusions and exclusions of past discourses. We analyse Kenya's post‐colonial agricultural policy discourse. Our analysis reveals a near‐exclusive focus on the promotion of agricultural modernisation based on industrial farm inputs, a bureaucratic state and/or 'the liberalised market'. It was with this thrust to modernise that smallholders (and other farmers) were generally seen as aligning. Smallholders' agency to diverge from modernisation was thus marginalised in the policy discourse. Overall then,  the promotion of diverse agroecological and other farmer‐led directions of development was largely missing from Kenya's policy landscape.